Hadrian and Gades: A Family Relationship - González-Conde Puente, Mª Pilar (Gerión. Revista de Historia Antigua, 2021)
This work is about Hadrian’s relationship with his maternal family and, through it, with the city of Gades (Cádiz, Spain), the city from which she came. The figure of L. Iulius Ursus Servianus, her sister’s husband, obviously had a very important role in this relationship. Through the treatment in the classical sources, the evolution of this relationship is analyzed from the final moments of the Nerva’s government until the death of Servianus, to determine to what extent it had relevance in some Hadrian’s decisions.